ENVIRONMENT AND PRODUCTIVITY NEXUS: AN EMPERICAL ANALYSIS OF A PRODUCTIVE ORIENTED ORGANISATION - Ibojo Bolanle Odunlami (European Scientific Journal, ESJ, 2012)
This issue of productivity cannot be over emphasized when considering the nature of an objective minded organization. Although there are different ways of measuring the level of productivity of organizations, yet, it is a great tool that must be considered when analyzing the level of growth and development of an organization. Organizations are integral parts of the environment, thereby can be influenced by the forces and actors of the environment. This study tends to assess the effect of environment on organizational productivity. Although no organization bargains for low productivity, but this can occur if the organization fails to acknowledge and incorporate the vital nature of environmental forces into its management portfolio. This research adopted primary and secondary sources of data. The primary data involves the use of questionnaires while the secondary data envelopes the use of journals, internet and relevant literature materials. The data was analyzed in percentages while the hypotheses were tested using correlation coefficient. The results show that there is a significant relationship between environment and employees productivity. More so, there is also a significant relationship between motivation and employees productivity. It is hereby concluded that environmental factors serve as vital tools for the survival, growth and development of organizations, and thereby should be incorporated in management decision making. In line with this study, it is recommended that management should not only motivate employees but only intensity the degree of the cordial relationship with employees. More so, organizations must constantly watch and monitor the dynamic nature of the environment and provide training and refresher courses that will enhance employees’ potential.